Education with Augmented Reality - Bhagyashri Shinde; Dr. Dinesh Patil (International Journal of Engineering and Management Research, 2022)
Technology in education has impacted many ways in student's life to learn enthusiastically by giving better and more than expected results. Some research stated that technology will create a passive process if it doesn't promote critical thinking. To support the statement Augmented Reality (AR) has shown the best potential to make learning more interactive and easy. It's because of the feature of AR that lets us interact with things in virtual and real-time. Therefore this paper represents the idea of using AR in education.